If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u + (u + -2) = 10 Reorder the terms: 3u + (-2 + u) = 10 Remove parenthesis around (-2 + u) 3u + -2 + u = 10 Reorder the terms: -2 + 3u + u = 10 Combine like terms: 3u + u = 4u -2 + 4u = 10 Solving -2 + 4u = 10 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4u = 10 + 2 Combine like terms: -2 + 2 = 0 0 + 4u = 10 + 2 4u = 10 + 2 Combine like terms: 10 + 2 = 12 4u = 12 Divide each side by '4'. u = 3 Simplifying u = 3
| y^2-10y=-23 | | (x-2)5=0 | | (x-2)5=x | | 6a^3+15a= | | 5x+3y=-8 | | 5r^2-26r=24 | | 4b^2-17b=15 | | 18.3x-7.6=8.4x-14.6 | | 3t^2-13t-16=0 | | (2x+1)(x-4)(3x+5)=0 | | 5x-2(x-2)=11 | | -8x+20+10x=42 | | 3x-7=9+7x | | x+8=-2-x | | 15x^2+2xy-8y^2=0 | | 80x=-280 | | 100x=400 | | 2(x+2)=3(3x-4) | | 23x+10=28x+30 | | 21x+2=21x+11 | | 5-(2x+4)=3-(3x+2) | | x+24=24-y | | 12y^2-19y-21=0 | | x^4+4x=-c | | x^4+4x=c | | 4x+1+4c=5c-3x+6 | | 6y^2+23y+7=0 | | 3y^2-11y+10=0 | | 5x-8+3(2X-5)= | | 4y^2+9y+5=0 | | -2(x+3)=-2(x+5)-4 | | -2(x+3)=-2(x+2)-4 |